Synopsis: Challenges to soya export promotion: An institutional analysis of trade policy in Malawi - Aberman, Noora-Lisa; Edelman, Brent (International Food Policy Research Institute, 2015)
In spite of relatively strong per capita Gross Domestic Product (GDP) growth, Malawi continues to face a variety of economic challenges, including severe balance of payments shortfalls, fiscal deficits, and pervasive poverty. Its economy relies heavily on agriculture, which contributes one-third of the country’s GDP and make up 90 percent of export revenues. Tobacco alone accounts for 60 percent of Malawi’s exports by value (ITC 2014). The country’s reliance on tobacco as its major export revenue earner leaves its economy vulnerable to exogenous shocks. Furthermore, with the official poverty rate at 50 percent of the population and an estimated 1.9 million people having been at risk of food insecurity in 2013-2014, economic shocks potentially can have dire human consequences (FEWSNET 2013).